Analisis Organisasi Pelaksana Program Pelayanan IMS Di Puskesmas Kabupaten Sukoharjo (Analysys Of Organisation Of IMS Services Program In Sukoharjo Public Health Center) - Surati Ningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2016)
Abstract : IMS incidence in a key populations found in Sukoharjo district on January-December 2014 include 36 cases. While the findings of HIV and AIDS cases in Sukoharjo district based on the risk group in 2014 which was found 2 cases in WPS group, 6 cases of transvestites, LSL 27 cases, 12 cases of customer and partner 9 cases. Sukoharjo Regency Health Office has established two health centers as IMS clinics, this study aims to analyze the organisation of IMS program in Sukoharjo public Health Center. This research is qualitative using in-depth interviews and direct observation. Key informants in this study were eight officers executing the program is doktor, nurse/midwife, laboratorium officer and administrative officer. Informant triangulation is the head of public health center, head of P2 department on DKK. The data analysis techniques are by analyzing the content, including in-depth interviews with informants, it was processed and then the data were analyzed. The results showed that at the health center IMS services has already had organization structure, there is unsupportable program officer, human resources are sufficient in quantity, but in quality one officer has not received training and found report delays in one of the health centers. The proposed recommendation is to optimization of human resources, allocation of special funds by the Government for fulfilling infrastructure, controlling report from health centers and intensive supervising by providing feedback from DKK to public health centers in Sukoharjo.Keywords : Organitation, IMS Service Program Abstrak : Kejadian IMS pada populasi kunci yang ditemukan di kabupaten Sukoharjo pada Januari – Desember tahun 2014 didapati 36 kasus. Sedangkan temuan kasus HIV dan AIDS di kabupaten Sukoharjo berdasarkan kelompok resiko tahun 2014 didapatkan pada kelompok WPS sebanyak 2 kasus, waria 6 kasus, LSL 27 kasus, pelanggan 12 kasus dan pasangan risti 9 kasus. Dinas Kesehatan Kabupaten Sukoharjo telah menetapkan 2 puskesmas sebagai klinik IMS, penelitian ini bertujuan untuk menganalisis organisasi pelaksana program pelayanan IMS Puskesmas Kabupaten Sukoharjo. Jenis penelitian ini adalah kualitatif dengan menggunakan wawancara mendalam, observasi dan telaah dokumen. Informan utama dalam penelitian ini adalah delapan petugas pelaksana program yaitu dokter, perawat / bidan, petugas laboratorium dan perugas administrasi. Informan triangulasi kepala puskesmas, Kasi P2 DKK. Teknik analisis data dengan analisis konten, meliputi wawancara mendalam dengan informan diolah kemudian dilakukan analisis data. Hasil penelitian menunjukkan bahwa di Puskesmas Pelayanan IMS sudah mempunyai stuktur organsasi, satu petugas pelaksana program yang kurang mendukung, SDM secara kuantitas sudah memadai dan secara kualitas satu petugas belum mendapat pelatihan dan didapati keterlambatan pelaporan. Saran yang direkomendasikan adalah optimalisasi SDM, pengalokasian dana khusus oleh Pemda untuk pemenuhan sarana prasarana, penertiban pelaporan dari Puskesmas dan pembinaan yang intensif dengan pemberian umpan balik oleh DKK kepada Puskesmas di Kabupaten Sukoharjo.Kata kunci : Organisasi, Program Pelayanan IMS